Drosophila TRP channels. - Montell, C. (Pfluger's Archiv (European Journal of Physiology), 2005)
The transient receptor potential (TRP) superfamily comprises a large group of related cation channels that display surprising diversity in the specific modes of activation and cation selectivities. However, a unifying theme is that many TRP channels play important roles in sensory physiology. The superfamily includes 28 mammalian members, which are subdivided into multiple subfamilies. Each of these subfamilies is represented by at least one of the 13 members in Drosophila, suggesting common evolutionary relationships. In recent years it has become clear that TRP channels in flies and mammals participate in similar sensory modalities. These include, but are not limited to, hearing, thermosensation, and certain specialized types of vision. With the recent flurry of new studies, 9 out of the 13 TRPs have been addressed in various contexts. As a result, the repertoire of biological roles attributed to Drosophila TRPs has increased considerably and is likely to lead to many additional surprises over the next few years.